2003
DOI: 10.1097/00007691-200310000-00008
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Use of a Simultaneous HPLC Assay for Indinavir, Saquinavir, Ritonavir, and Nelfinavir in Children and Adults

Abstract: Protease inhibitor (PI) monitoring may improve the care of human immunodeficiency virus (HIV)-infected patients; however, pediatric data are limited. A high-performance liquid chromatographic (HPLC) assay developed for the simultaneous determination of indinavir, ritonavir, saquinavir, and nelfinavir in 0.2 mL of plasma was used to quantify PI concentrations in HIV patients. The reliability, sensitivity, and specificity of the assay were first verified in stored adult samples. Later, blood collected prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…When antiretroviral drugs are administered at the recommended dose, plasma concentrations are expected in the 0.3 to 8.2 mg/ml range for APV, 12) the 0.2 to 10 mg/ml range for ATV, 17) the 0.1 to 7.7 mg/ml range for IDV, 18,19) the 5.5 to 9.6 mg/ml range for LPV, 12) the 0.1 to 4.0 mg/ml range for NFV, 18,20) the 0.1 to 11.2 mg/ml range for RTV, 18,20) the 0 to 0.2 mg/ml range for SQV, 18) and the 1 to 4 mg/ml range for EFV. 21) Our method successfully covers these regions with good precision and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…When antiretroviral drugs are administered at the recommended dose, plasma concentrations are expected in the 0.3 to 8.2 mg/ml range for APV, 12) the 0.2 to 10 mg/ml range for ATV, 17) the 0.1 to 7.7 mg/ml range for IDV, 18,19) the 5.5 to 9.6 mg/ml range for LPV, 12) the 0.1 to 4.0 mg/ml range for NFV, 18,20) the 0.1 to 11.2 mg/ml range for RTV, 18,20) the 0 to 0.2 mg/ml range for SQV, 18) and the 1 to 4 mg/ml range for EFV. 21) Our method successfully covers these regions with good precision and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of saquinavir from plasma samples was performed according to the method of Walson et al (2003). The frozen plasma samples were thawed and vortexed.…”
Section: Extraction Of Saquinavir From Plasmamentioning
confidence: 99%
“…Quantitative determination of SQV from Caco-2 cell monolayers by HPLC-UV was reported by Ucpinar and Stavchansky (2003). Walson et al (2003) developed a simultaneous assay of indinavir, saquinavir, ritonavir and nelfinavir in children and adults by HPLC for clinical use. Berginc et al (2010) studied the pharmacokinetic method of SQV while Buchanan et al (2008) reported pharmacokinetics of saquinavir after intravenous and oral dosing of saquinavir hydroxybutenyl-β-cyclodextrin formulations.…”
Section: Saquinavir (2s)-n-{(2s3r)-4-[(3s)-3-(tert-butylcarbamoyl)-mentioning
confidence: 99%